Structural characterization of blends containing both PVDF and natural rubber latex - Simoes, R. D.; Job, A. E.; Chinaglia, D. L.; Zucolotto, V; Camargo, J. C.; Alves, M.; Giacometti, J. A.; Oliveira, O. N.; Constantino, CJL (Wiley-Blackwell, 2005)
Films containing different volumes of latex of natural rubber (NR) in a fixed mass of poly (vinylidene fluoride) (PVDF) powder were fabricated by compressing under annealing a mixture of both materials without using any solvent. This is an important issue keeping in mind that these films have to be used in the future as biomaterials in different applications once the solvents that are used to dissolve the PVDF become toxic to human. The films with different percentage of latex in PVDF were characterized using microRaman scattering and Fourier transform infrared absorption (FTIR) spectroscopies, thermomechanical techniques using thermogravimetry (TG), differential scanning calorimetry (DSC), dynamical-mechanical analysis (DMA) and scanning electron microscopy (SEM). The results showed that the latex of NR and PVDF do not interact chemically, leading to the formation of a polymeric blend with high thermal stability and mechanical properties suitable for applications involving bone (prostheses, for instance). Besides, the results recorded using the micro-Raman technique revealed that for a fixed amount of PVDF the higher the amount of latex in the blend, the better the miscibility between both materials. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: PVDF; natural rubber; blends; micro-Raman thermal analysis